The Need For Mandatory Autopsy Teaching In Forensic Medicine For Medical Students - Nurul Kharmila Abdullah; Nur Arina Ahmad; Shalinawati Binti Ramli; Nadiawati Abdul Razak (Universidade de sao Paulo, Hospital Universitari, 2025)
Autopsy and Case Reports, Volume 14